A Pragmatic Analysis Of Love Expression ReflectedIn The Last Promise Novel By Richard Paul Evans - Afnani, Ahlam Veryya, Agus Wijayanto. Ph.D, Dra. Siti ZuhriyahAriatmi, M. Hum (2013)
This study deals with the linguistic form of love expressions in the last promise novel, the illocutionary meaning of love expressions in the last promise novel, and the politeness strategy of love expression in the last promise novel. The type of this research is descriptive qualitative research in which the object is love expressions in The Last Promise novel by Richard Paul Evans. In collecting data, the writer uses documentation method. The data were the written text of love expression utterance used in The Last Promise novel. The data of variations of linguistic form were analyzed by Marcella Frank, the illocutionary meanings were analyzed by Austin, and the politeness strategies were analyzed by Brown and Levinson. The result of the study shows that, (1) there are three variations of linguistic form for love expressions, they are declarative sentence (I wanted to do something special for you), interrogative sentence (how about if we just hug?), and imperative sentence (promise me you will never leave me again). (2) there are six illocutionary meaning of love expressions, namely showing affection (I love you Eliana, with all my heart I love you), showing care (but, be careful), showing engagement (I will always love you), showing persuasion (have you ever seen a moon like that?), showing eagerness (I want to be alone with you), expressing compliment (you have beautiful hands). (3) there are three types of politeness strategies for love expression, they are Bald on record strategy (I won't leave him), Positive politeness strategy (I'm glad you came to Rendola, Ross), Negative politeness strategy (I didn't mean to hurt you).